2016
DOI: 10.1016/j.regsciurbeco.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

How do agricultural markets respond to radiation risk? Evidence from the 2011 disaster in Japan

Abstract: Since the explosion of the Fukushima Daiichi Nuclear Power Plant in March 2011, public anxiety surrounding the radioactive contamination of food and the environment has become widespread. This article examines how the price of vegetables in the Tokyo Metropolitan Central Wholesale Market was impacted in the wake of the nuclear accident. This study exploits the quasi-experimental condition generated by this accident to test the market price change using monthly panel data on the price of six types of fresh vege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Our study is related to the large literature investigating the housing capitalisation effects of changes in local amenities. While our focus on the combustible cladding crisis is unique, other studies have looked at a range of related events, such as transport infrastructure (Lieske et al, 2021;Melser, 2020), prospective sea-level rise (Bernstein et al, 2019;Keys and Mulder, 2020), exposure to flood risks (Rambaldi et al, 2013), changes in school quality or characteristics (Haisken-DeNew et al, 2018;Melser et al, 2021), the effect of visual amenities such as wind farms (Gibbons, 2015) and the impact of informational shocks about nuclear power resulting from the 2011 Fukushima accident (Bauer et al, 2017;Fink and Stratmann, 2015;Kawaguchi and Yukutake, 2017;Tajima et al, 2016;Tanaka and Zabel, 2018). A key focus of these studies is quantifying the overall effect on prices of the events of interest.…”
Section: Related Literaturementioning
confidence: 99%
“…Our study is related to the large literature investigating the housing capitalisation effects of changes in local amenities. While our focus on the combustible cladding crisis is unique, other studies have looked at a range of related events, such as transport infrastructure (Lieske et al, 2021;Melser, 2020), prospective sea-level rise (Bernstein et al, 2019;Keys and Mulder, 2020), exposure to flood risks (Rambaldi et al, 2013), changes in school quality or characteristics (Haisken-DeNew et al, 2018;Melser et al, 2021), the effect of visual amenities such as wind farms (Gibbons, 2015) and the impact of informational shocks about nuclear power resulting from the 2011 Fukushima accident (Bauer et al, 2017;Fink and Stratmann, 2015;Kawaguchi and Yukutake, 2017;Tajima et al, 2016;Tanaka and Zabel, 2018). A key focus of these studies is quantifying the overall effect on prices of the events of interest.…”
Section: Related Literaturementioning
confidence: 99%
“…Their results also indicated less reputation damage in regions where consumers of Fukushima peaches were present prior to the nuclear accident. Tajima et al (2016) found that reputation damage resulted in a 10-36 per cent decrease in prices of vegetables after the nuclear accident in the Fukushima prefectureas compared to counterfactual estimates that included absence of perceived radiation risk. The effect on prices lasted for four years.…”
Section: Impacts Of the Disastersmentioning
confidence: 99%
“…He found that most vegetables produced in Fukushima lost their value and share in the Tokyo market after the nuclear accident and that this trend worsened in the second year compared with the first. Recently, Tajima et al () conducted a hedonic regression analysis to assess the impact of the nuclear accident on fresh vegetable prices in the Tokyo wholesale market. They found that the price of vegetables grown in Fukushima prefecture decreased by 10–36% after the nuclear accident and that these price reductions persisted for three years thereafter.…”
Section: Literature Backgroundmentioning
confidence: 99%
“…The results of tests conducted by the Japanese government and non‐government organisations demonstrated that many agricultural products (including peaches, which are the focus of this paper) produced in the Fukushima prefecture were not contaminated by radiation. The results of these tests were published on government websites (MAFF, ) and the information was widely disseminated and discussed on public media channels including television, radio, newspapers, magazines and websites (Tajima et al , ). In addition, retailers also conducted independent surveys to examine food safety and reported the safety of Fukushima products (AEON, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation